Pengaruh Modal Kerja Yang Ditinjau Dari Perputaran Kas, Perputaran Piutang Dan Perputaran Persediaan Terhadap Return On Asset (ROA) Pada Perusahaan Sub Sektor Jasa Komputer Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2013 – 2017 - Heriyanto, Ahmad Rifai, Titin Ruliana (EKONOMIA, 2020)
This study aims to prove: Is working capital viewed from cash turnover affecting the level of Return On Assets (ROA) in Computer Services Sub Sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2013-2017 ?, Is working capital reviewed from accounts receivable turnover affects the level of Return On Assets (ROA) in Computer Services Sub Sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2013-2017 ?, Does working capital reviewed from inventory turnover affect the rate of Return On Assets (ROA) Computer Services Sub Sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2013-2017 ?, Are working capital reviewed from cash turnover, accounts receivable turnover, inventory turnover affect the level of Return On Assets (ROA) in companies of the Computer Services Sub Sector listed on the Indonesia Stock Exchange (IDX) for the period 2013-2017.The theoretical basis of this research is financial management which focuses on cash turnover, inventory turnover turnover and Return On Assets (ROA). the analytical tool used is ratio and linear multiple regression.The results of the study of the effect of cash turnover on Return On Assets (ROA) concluded with a sample test t, it is known that there is a positive and significant influence on Return On Assets (ROA). thus hypothesis 1 is accepted. For accounts receivable turnover and inventory turnover on Return On Assets (ROA) concluded by sample test t, it is known that there is no positive and no significant effect on Return On Assets (ROA). Thus hypotheses 2 and 3 are rejected. And for the results of the study the effect of cash turnover, accounts receivable turnover and inventory turnover on Return On Assets (ROA) concluded with a sample test f, it is known that there is a positive and significant influence on Return On Assets (ROA). thus hypothesis 4 is accepted.